VALUE-BASED STRATEGIC MANAGEMENT: INTEGRATING ISLAMIC ETHICS IN EDUCATIONAL STRATEGIC PLANNING - Zam zam Lukmanul Jamil; Ujang Miftahudin; Ara Hidayat (LP2M IAIN Sultan Amai Gorontalo, 2025)
This research aims to examine the integration of Islamic ethics in value-based strategic management as a holistic approach in educational strategic planning. The main problem raised is the lack of application of Islamic values in education management, which has an impact on the less than optimal achievement of Islamic education goals. This research uses the literature study method by analysing relevant literature, theories and concepts. The results show that the integration of Islamic values, such as trustworthiness, justice, ihsan and deliberation, provides an effective framework to improve efficiency, accountability and sustainability in education management. This approach not only addresses the challenges of modernization, but also maintains the spiritual identity of Islamic educational institutions. The findings are expected to serve as a practical guide for educational institutions, researchers, and policy makers in managing value-based education.